Empreendedores MEI e ME: análise da educação para o empreendedorismo em marketing à luz do conceito de sistema de marketing - Carrazzoni, Rebeca Sá do Nascimento (2023)
Individual microentrepreneurs (MEI) and microenterprises (ME) face constant challenges to remain in the market, however, the positive view of entrepreneurship sometimes makes it difficult to plan actions that actually improve their reality. These difficulties were reinforced by constant changes in the environment and new consumption patterns, requiring new knowledge and new skills to survive in an uncertain scenario. With the increase in demand, technological facilities and digitization, education for entrepreneurship gained prominence with the business public that was already active in the market, envisioning the development of skills to manage their businesses, which boosted the diversification of offers and the increase of management solutions. This movement in search of knowledge in marketing and management evidenced the performance of professionals with practical and agile teachings, infallible methods and easyto-understand tools, as well as heroic stories of success and overcoming, which are classified as stage entrepreneurs, lecturers of marketing and successful entrepreneurs. That said, the problem of this thesis addresses this context from a Macromarketing perspective and in the light of the concept of the marketing system. Therefore, the thesis argues that the marketing offer of entrepreneurship education (EE) has a structure and functioning that need to be delineated and analyzed to delimit the potential imbalances and resulting externalities, and thus aims to analyze entrepreneurship education in marketing for MEI and ME entrepreneurs, particularizing the vision of the entrepreneurship education marketing system (SMEE). In order to understand and be able to manage the marketing of their businesses, entrepreneurs sought professionals to teach and translate marketing demands, which highlighted the gap between the theoretical marketing of the academy and the marketing applied in practice, affecting the vision and credibility of the area before the market, from incorrect conceptions and distortion of its function. In this way, the thesis delimited the agents involved, the inputs, functioning and outputs of the SMEE, understanding their exchange relations with an emphasis on the offer in marketing. After the theoretical construction, the field research pioneered this system, still little explored, through a qualitative approach, based on participant observation techniques and semi-structured interviews. In addition, 23 interviews were carried out between entrepreneurs and professionals, which resulted in the particular characterization of the SMEE, configuration of the marketing offer, identification of the exchange relations in the SMEE and the positive and negative outputs. Likewise, potential imbalances in the SMEE were highlighted in the attempt to contribute to an improvement of the system and more adequate offers, in order to benefit all those involved. Finally, the research met its objectives and generated contributions through discussions about the conception of marketing for the market, marketing practices undertaken in this context and change of attitude in the performance of academics in the face of the needs of practitioners.